Effect of Some Immunomodulators Use Together with PPR Vaccine on Immune system in Morkaraman Sheep - Aydın, Ö; Aktaş, MS (Journal of the Hellenic Veterinary Medical Society, 2023)
In this study, it was aimed to investigate the effects of vitamin C (Vit-C), vitamin D (Vit-D), levamisole (LMS), inactivated parapoxvirus ovis (iPPVO) and corynebacterium cutis lysate (CCL) on the immune system in Morkaraman sheep on which the peste des petitis ruminant (PPR) vaccine was administered. In the Group B (Vit-D + PPR vaccine), in terms of IgG, when compared 0th, 14th, 21st and 28th, the values of the day 7th were determined to be significantly higher (P<0.01). In comparison to overall evaluation based on groups of IgG assay, the Group C (LMS + PPR vaccine) value was determined to be significantly higher than the Group F (PPR vaccine), Group A (Vit-C + PPR vaccine), Group B and Group D (iPPVO + PPR vaccine) values (P<0.01). In terms of IgM, when days among groups are compared, the highest value was determined on the 7th day in the Group A and this value was determined to be significant according to the 7th day Group F, Group E (CCL + PPR vaccine) and Group D values (P<0.01). The application of LMS at the stated dose had positive effects on the immune system due to changes in both IgM and IgG values, and Vit-C application at the stated dose had a partially positive effect only due to changes in IgM value; the administration of Vit-D, iPPVO and CCL at the stated doses did not have any positive effect on the immune system.